NILAI-NILAI KEHIDUPAN KRISTIANI MENURUT KISAH PARA RASUL 4:32-37 - Yulia Darlin; Ragil Kristiawan; Rudyanto Chandra Saputra (JOURNAL of THEOLOGICAL STUDENTS, 2021)
One of the ways to create togethernessin a chuch is if the congregation applies the values of the Christian life. A chuch that applies the values of Christian life will create a sense of intimacy and the congregation will promote togetherness. Therefore this research was conducted to find out how the togetherness values of the Christian life according to Acts 4:32-37 in the Muria Indonesia Christian Church in Puri Anugerah Semarang. This research is a qualitative research with one variable. From the question of the problem, the results show that the values of the Christian life according to Acts 4:32-37 at the Muria Indonesia Christian Church in Puri Anugerah Semarang have all been well understood, even though the two values are still lacking in their application.